Propuesta de la red de alcantarillado sanitario para la parroquia Borbón en la provincia de Esmeraldas - Ayovi Moreira, Gilson Josue (2024)
The objective of the project is the Design of the Sanitary Sewer network of the Borbón Parish in the Province of Esmeraldas, in order to fulfill and develop our design, a methodology with a mixed approach was implemented. Quantitative because it was established in the collection of housing and population data, in turn with the qualitative approach since the surveys were carried out to have a clearer knowledge of the population information. Population data was collected to know if the project will be accepted. A sample of 365 surveys was carried out and there was a population of 7,696 inhabitants. The analysis of the Borbón parish was carried out and there are sectors that are not connected to the current sewage network, as they are informal settlements using latrines or septic tanks. Therefore, the design of the Sanitary sewage network is proposed considering the calculations for a population growth of 15,320 inhabitants with a total of 3064 homes and with an extraordinary maximum flow of 136.60 liters/sec., with this design the aim is to guarantee the correct operation of the network, thus contributing to the community and the environment by reducing environmental pollution in the Borbón parish.